Ecotourism demand forecasting at National Park Kuala Tahan, Pahang - Noratikah, Abu; Megat Muhammad Afif, Megat Muainuddin; Wan Nur Syahidah, Wan Yusoff; Zuhaimy, Ismai (Universiti Malaysia Pahang, 2019)
Tourism forecasting can lead to an important element in tourism industry to ensure that each investment by individuals, companies and government was worth it. From economy perspective, ecotourism is a growing business nowadays and can be an important indicator to the tourism industry. Hence, this study attempt to forecast the ecotourism product demand in Pahang based on number of tourist arrivals in National Park Kuala Tahan, Pahang. Box-Jenkins (Seasonal ARIMA) model is used to make analysis and forecast of the number of international and domestic tourist since 2013 until present. The accuracy and validation of the results is measured using mean absolute percentage error (MAPE). Results obtained by applying the proposed model and numerical calculation shows that Seasonal ARIMA models is effective for forecasting the number of tourist arrivals in National Park Kuala Tahan. The best model in forecasting ecotourism product demand in Pahang is   12 SARIMA 0,0,1 2,0,1 with MAPE value 13.92%.